PELATIHAN PENERAPAN KURIKULUM MERDEKA BELAJAR DI DALAM KONTEKS PENGAJARAN DAN PEMBELAJARAN BAHASA INGGRIS - Mali, Yustinus Calvin Gai; Ragawanti, Debora Tri; Mambu, Joseph Ernest; Isharyanti, Neny (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
This article reports a community service program held by the Master’s Program in English Language Education at the Faculty of Language Arts, Universitas Kristen Satya Wacana, in collaboration with the Salatiga Education Department. The program was in the form of teachers’ training about best practices of implementing the Merdeka Belajar curriculum in the English language teaching and learning practices. Thirty-six (36) English teachers in junior high schools in Salatiga participated in this training from July 31 – August 1, 2023. There were five main sessions in the training, namely (1) critical thinking and Merdeka belajar, (2) differentiated instruction in the ELT contexts/EFL classrooms, (3) digital text-based learning for teaching English in secondary schools, (4) best practices in technology-enhanced language learning, and (5) the implementation of Merdeka Belajar curriculum: A reflection. Brief descriptions of what the presenters discussed in each of their sessions, directions for future community service programs, and research are presented.